Low and High Molecular Weight FGF-2 Have Differential Effects on Astrocyte Proliferation, but Are Both Protective Against Aβ-Induced Cytotoxicity - Chen, Xi; Li, Zhaojin; Cheng, Yong; Kardami, Elissavet; Loh, Y. Peng (Frontiers in Molecular Neuroscience, 2020)
Astrocytes are the most abundant type of glial cells in the brain, and they play a key role in Alzheimer’s disease (AD). Fibroblast Growth Factor-2 (FGF-2) has been implicated as a potential therapeutic agent for treating AD. In the present study, we investigated the protective effects of low molecular weight (17KDa) and high molecular weight (23KDa) forms of FGF-2 on Aβ1-42-induced toxicity, and proliferation in astrocytes. We show that both isoforms of FGF-2 have similar protective effects against Aβ1-42-induced cytotoxicity in primary cultured cortical astrocytes as measured by LDH release assay. Additionally, 17KDa FGF-2 significantly promoted astrocyte proliferation as measured by Trypan Blue, DRAQ5 staining, ki67 and Edu immunocytochemistry, but not 23kDa FGF-2. Furthermore, our results demonstrated that AKT signaling pathway was required for the protective and proliferative effects of FGF-2. Downstream effector studies indicated that 17kDa FGF-2 promoted astrocyte proliferation by hyper-phosphorylation of AKT at Thr308 residue and enhanced expression of c-Myc, Cyclin D1, Cyclin E. Furthermore, our data suggest that Cyclin D1 is required for the proliferative effect of LMW FGF2 in astrocytes. Taken together, our findings showing differential effects of 23kDa and17kDa isoforms of FGF-2 on astrocyte protection and promotion of proliferation, provide important information for determining the form of FGF-2 that will be most appropriate for potential treatment of AD.